2016
DOI: 10.1016/j.mce.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and regulatory architecture of ERBB3-type 1 diabetes susceptibility locus

Abstract: a b s t r a c tThe study aimed to explore the role of ERBB3 in type 1 diabetes (T1D). We examined whether genetic variation of ERBB3 (rs2292239) affects residual b-cell function in T1D cases. Furthermore, we examined the expression of ERBB3 in human islets, the effect of ERBB3 knockdown on apoptosis in insulinproducing INS-1E cells and the genetic and regulatory architecture of the ERBB3 locus to provide insights to how rs2292239 may confer disease susceptibility. rs2292239 strongly correlated with residual b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…The most robust association was reported with the Erb‐B2 Receptor Tyrosine Kinase 3 (ERBB3) rs2292239 T1D risk SNP and HbA1c level. The association remains significant after adjusting for insulin dose, gender, age at onset, and diabetes duration, but this finding has not been replicated yet. The Protein Tyrosine Phosphatase Non‐receptor type 22 (PTPN22) T1D risk allele was associated with HbA1c level, but this finding was not replicated in an independent study that used the insulin dose‐adjusted HbA1c measure (IDAAC), defined by Mortensen et al in 2009 .…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The most robust association was reported with the Erb‐B2 Receptor Tyrosine Kinase 3 (ERBB3) rs2292239 T1D risk SNP and HbA1c level. The association remains significant after adjusting for insulin dose, gender, age at onset, and diabetes duration, but this finding has not been replicated yet. The Protein Tyrosine Phosphatase Non‐receptor type 22 (PTPN22) T1D risk allele was associated with HbA1c level, but this finding was not replicated in an independent study that used the insulin dose‐adjusted HbA1c measure (IDAAC), defined by Mortensen et al in 2009 .…”
Section: Resultsmentioning
confidence: 79%
“…These candidate gene association studies have never been or have been poorly replicated, except for angiotensin I converting enzyme (ACE) gene . Five of the 13 selected studies reported significant or suggestive associations, which were however never replicated …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…rs4759229 is in perfect LD with T1D risk SNP rs2292239, overlaps a known enhancer region and has a long range interaction signal with an antisense lncRNA AC008079.1 (Ensembl ID: ENSG00000187979) located at USP18 locus on chromosome 22. In a recent study, we proposed that the ERBB3 SNP rs2292239 and its proxy SNPs in perfect LD rs3741499 and rs4759229 are putatively functional based on the overlapping open chromatin marks, TFBs and DNase I hypersensitivity peaks [79]. We further showed that SNP rs4759229 overlaps a known enhancer element and is in the vicinity of several lncRNA transcripts overlapping ERBB3 locus.…”
Section: Main Textmentioning
confidence: 99%